Novel and known ribosomal causes of Diamond-Blackfan anaemia identified through comprehensive genomic characterisation. Issue 6 (9th March 2017) - Mirabello, Lisa; Khincha, Payal P; Ellis, Steven R; Giri, Neelam; Brodie, Seth; Chandrasekharappa, Settara C; Donovan, Frank X; Zhou, Weiyin; Hicks, Belynda D; Boland, Joseph F; Yeager, Meredith; Jones, Kristine; et al.
Abstract : Background: Diamond-Blackfan anaemia (DBA) is an inherited bone marrow failure syndrome (IBMFS) characterised by erythroid hypoplasia. It is associated with congenital anomalies and a high risk of developing specific cancers. DBA is caused predominantly by autosomal dominant pathogenic variants in at least 15 genes affecting ribosomal biogenesis and function. Two X-linked recessive genes have been identified. Objectives: We aim to identify the genetic aetiology of DBA. Methods: Of 87 families with DBA enrolled in an institutional review board-approved cohort study (ClinicalTrials.gov Identifier:NCT00027274 ), 61 had genetic testing information available. Thirty-five families did not have a known genetic cause and thus underwent comprehensive genomic evaluation with whole exome sequencing, deletion and CNV analyses to identify their disease-associated pathogenic variant. Controls for functional studies were healthy mutation-negative individuals enrolled in the same study. Results: Our analyses uncovered heterozygous pathogenic variants in two previously undescribed genes in two families. One family had a non-synonymous variant (p.K77N) in RPL35 ; the second family had a non-synonymous variant (p. L51S) in RPL18 . Both of these variants result in pre-rRNA processing defects. We identified heterozygous pathogenic variants in previously known DBA genes in 16 of 35 families. Seventeen families who underwent genetic analyses are yet to have a genetic cause of disease identified. Conclusions: Overall, heterozygous pathogenic variants in ribosomal genes were identified in 44 of the 61 families (72%). De novo pathogenic variants were observed in 57% of patients with DBA. Ongoing studies of DBA genomics will be important to understand this complex disorder.